2016
DOI: 10.1039/c6nj01941b
|View full text |Cite
|
Sign up to set email alerts
|

Optimised synthesis of monoanionic bis(NHC)-pincer ligand precursors and their Li-complexes

Abstract: A straightforward preparation of bis(imidazol)carbazole 4 from carbazole, its transformation to various bis(imidazolium) salts and their deprotonation to Li carbene complexes is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…In the 13 C NMR spectrum, the carbene signal of the free NHC moiety would be expected at around 215 ppm. In our case, the signal at 204.5 ppm is characteristic for a coordination of the carbene moiety to lithium ions as it has been reported for other Li(bimca) complexes [ 13 ]. However, typically, the carbene signals of lithium complexes are shifted by about 20 ppm to higher field compared to the respective free carbenes.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…In the 13 C NMR spectrum, the carbene signal of the free NHC moiety would be expected at around 215 ppm. In our case, the signal at 204.5 ppm is characteristic for a coordination of the carbene moiety to lithium ions as it has been reported for other Li(bimca) complexes [ 13 ]. However, typically, the carbene signals of lithium complexes are shifted by about 20 ppm to higher field compared to the respective free carbenes.…”
Section: Resultssupporting
confidence: 81%
“…When we reported on the improved synthesis of the so-called bimca ligand [ 15 ] (1,8- b is( im idazolin-2-ylidene)-3,8-di- tert -butyl ca rbazolide), a monoanionic CNC ligand, we also showed that a still relatively concentrated reaction mixture of 1,8-bis(imidazol-1-yl)-3,8-di- tert -butylcarbazol and 1,5-dibromopentane leads selectively to the bisimidazolium macrocycle 1a (Hbimca C5 )·2HBr [ 13 ]. However, until now, the coordination chemistry of this proligand remained unexplored.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Imidazolium salts are best known for their applications in catalysis [6,7], the field of ionic liquids [8][9][10], and antimicrobial properties [11,12]. Many NHC precursor has been put on designing [13][14][15], but the NHC precursor containing carbazole are quite rare [16,17]. There are two cations and four anions in the asymmetric unit.…”
Section: Commentmentioning
confidence: 99%
“…N-heterocyclic carbenes (NHCs) have become ubiquitous in transition metal chemistry, 1-3 catalysis [4][5][6] and for the stabilisation of reactive main group complexes. [7][8][9] Numerous studies over the last 30 years have expanded the structural and electronic diversity of NHCs, in an effort to fine-tune their properties. 1,4 Among the possibilities for derivatisation is the modification of the 4,5-position of the imidazole ring, which has been shown to impart an increase in aerobic stability, 10,11 an important step to achieving 'bottleable' NHCs.…”
Section: Introductionmentioning
confidence: 99%